أهمية تدريس مهارة الاستماع في مناهج اللغة العربية بالتعليم العام - عطاالله, عبد الحميد (جامعة الوادي - University of Eloued, 2023)
ملخص: يهدف هذا البحث إلى توضيح أهمية تدريس الاستماع في مناهج اللغة العربية بالتعليم العام، باعتماد مقاربة ديداكتيكية وصفية، حيث بينا مفهوم الاستماع وطبيعته، والهدف منه بشكل عام، ومن تدريسه بشكل خاص، كما بينا خصائص محتوى منهاج الاستماع، وكيفية تدريسه. وقد خلص البحث إلى أن الاستماع هو عملية معقدة، وهو من أهم فنون اللغة، فعليه يتوقف اكتساب اللغة الأولى وعملية التواصل، وأيضا تعلم اللغة واكتساب المعارف في مختلف المقررات التعليمية، لذا وجب تدريس الاستماع في مناهج اللغة العربية لرفع مستوى تحصيل المتعلمين بشكل عام؛ ويجب لذلك إعداد مقررات وكتب خاصة بالاستماع لكل مرحلة تعليمية؛ كما يجب إعداد المعلمين إعدادا خاصا لتحقيق الغرض من تدريس الاستماع. Abstract : This research aims to clarify the importance of teaching listening in Arabic language Curriculum in general education, by adopting a didactic and descriptive approach, where we explained the concept of listening and its nature, and its purpose in general, and its teaching in particular, as well as the characteristics of the content of the listening curriculum, and how to teach it. The research concluded that listening is a complex process, and it is one of the most important language arts. Where the acquisition of the first language and the communication depend on it, as well as language learning and acquiring knowledge in various educational courses, Therefore, it is necessary to teach listening in the Arabic language curriculum to improve the level of achievement in general; Listening courses and books should also be prepared for each educational stage; Teachers must also be specially prepared to achieve the purpose of teaching listening.
مقال
Keywords: تدريس ؛ لغة عربية ؛ مهارات لغوية ؛ استماع; Teaching; Arabic Language ; Language skills; listening.